Industrial Performance of Several Lachancea thermotolerans Strains for pH Control in White Wines from Warm Areas - Cristian Vaquero; Iris Loira; María Antonia Bañuelos; José María Heras; Rafael Cuerda; Antonio Morata (Microorganisms, 2020)
In the current scenario of climatic warming, the over-ripening of grapes increases the sugar content, producing flat and alcoholic wines with low acidity, high pH and low freshness. Additionally, a high pH makes wines more chemically and microbiologically unstable, requiring a higher sulphite content for preservation. Some strains of Lachancea thermotolerans can naturally lower the pH of wine by producing lactic acid from sugars; this pH reduction can reach 0.5 units. The industrial performance of four selected strains has been compared with that of two commercial strains and with that of Saccharomyces cerevisiae. The yeasts were assessed under variable oenological conditions, measuring lactic acid production and fermentative performance at two fermentation temperatures (17 and 27 °C), and in the presence or absence of sulphites (25 and 75 mg/L). Lactic acid production depends on yeast populations, with higher concentrations being reached when the microbial population is close to or above 7-log CFU/mL. A temperature effect on acidification can also be observed, being more intense at higher fermentation temperatures for most strains. Ethanol yield ranged from 7–11% vol., depending on the fermentation conditions (temperature and SO2) at day 12 of fermentation, compared with 12% for the S. cerevisiae control in micro-fermentations. The production of fermentative esters was higher at 27 °C compared with 17 °C, which favoured the production of higher alcohols. Volatile acidity was moderate under all fermentation conditions with values below 0.4 g/L.